Analisis Faktor-Faktor Yang Mempengaruhi Minat Generasi Milenial Dalam Berwakaf Tunai - Ummu Maziah; Emy Widyastuti (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
Abstract: The purpose of this study was to examine the effect of attitudes, subjective norms, beliefs and income on the interest in cash waqf in the millennial generation, a case study of the millennial generation in Semarang Regency. This type of research is a quantitative research. The population used is the districts in Semarang Regency. The sample was taken by purposive sampling technique with the criteria of the District having the highest number of endowments and millennials, while the number of samples was calculated using the Slovin formula which obtained a total sample of 100 respondents. The method of data collection is through the distribution of questionnaires which are then analyzed by Multiple Linear Regression. The results showed that partially attitude had no effect on interest in cash waqf in the millennial generation in Semarang Regency, while subjective norms, trust and income had an effect on interest in cash waqf in the millennial generation in Semarang Regency. Keywords: Attitude; subjective norm; trust, income, interest in cash waqf Abstrak: Tujuan penelitian ini adalah untuk menguji pengaruh sikap, norma subjektif, kepercayaan dan pendapatan terhadap minat berwakaf tunai pada generasi milenial studi kasus generasi milenial di Kabupaten Semarang. Jenis penelitian ini merupakan penelitian kuantitatif. Populasi yang digunakan yaitu wilayah-wilayah Kecamatan yang ada di Kabupaten Semarang. Sampel diambil dengan teknik Purposive sampling dengan kriteria Kecamatan yang memiliki jumlah wakaf dan milenial terbanyak, sedangkan jumlah sampel dihitung melalui rumus Slovin yang didapat jumlah sampel sebanyak 100 responden. Metode pengumpulan data melalui penyebaran kuesioner yang kemudian dianalisis dengan Regresi Linear Berganda. Hasil penelitian menunjukan bahwa secara parsial sikap tidak berpengaruh terhadap minat berwakaf tunai pada generasi milenial di Kabupaten Semarang, sedangkan norma subjektif, kepercayaan dan pendapatan berpengaruh terhadap minat berwakaf tunai pada generasi milenial di Kabupaten Semarang. Kata kunci: Sikap; norma subjektif; kepercayaan, pendapatan, minat berwakaf tunai